PENGARUH MODAL DAN PARTISIPASI ANGGOTA TERHADAP SISA HASIL USAHA (SHU) PADA KOPERASI PEGAWAI REPUBLIK INDONESIA UNIVERSITAS RIAU - Bs Saputra; Suarman '; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The aims of the study is to know the influencet of capital and the participation of members abaut (SHU) on KPRI University of Riau. The subject of this study is the members of KPRI University OF Riau, amount 94 people, the samples are taken by using the proportional sampling. The data are primary data and secondary data with data collection by using questionnaires and documentation. The echnique of analysis data I used is Multiple Linear Regression Analysis processed through SPSS 16.0 For Windows and Microsoft Excel program. The results of this study indicate that capital and the participation have significant effect on SHU. It’s meani the more higher capital from the member so the more hugher parcipation of member too and it wiil be increasing attainment of SHU. In other hard for increasing SHU, the operation need the motivation from the member by capital or the participation.Key Words: Cooperatives, Capital, Member Participation, the balance of the enterprises, SHU